An international comparison of asthma, wheeze, and breathing medication use among children. (December 2017) - Lawson, Joshua A.; Brozek, Grzegorz; Shpakou, Andrei; Fedortsiv, Olga; Vlaski, Emilija; Beridze, Vakhtangi; Rennie, Donna C.; Afanasieva, Anna; Beridze, Sophio; Zejda, Jan
Abstract: Background: There is variation in childhood asthma between countries with typically higher prevalence in "Westernized" nations. We compared asthma, respiratory symptoms, and medication prevalence in Eastern and Central European regions and Canada. Methods: We conducted a cross-sectional survey study of children (5–15 years) from one urban centre in each of Canada, Belarus, Poland, Republic of Georgia (Adjara), Republic of Macedonia, and Ukraine. Surveys were distributed through randomly selected schools to parents (2013–2015). Results: The prevalence of asthma differed by country from 20.6% in Canada to 1.5% in Ukraine (p < 0.001). This association remained after confounder adjustment. Except for Canada (58.7%) and Poland (42.5%), less than 10% of children with a history of wheeze had a diagnosis of asthma. Regardless of country, more than 50% of children with a diagnosis of asthma used breathing medications in the past year. Finally, except for Georgia (12.1%), all countries had a prevalence of ever wheeze above 20% (23.8% in Poland to 30.9% in Macedonia). Conclusions: Despite large differences in asthma prevalence, respiratory morbidity was more comparable suggesting asthma prevalence may be underestimated. Further validation of asthma diagnosis is needed. It is important to promote best diagnostic practices among first contact physicians. Highlights: Childhood asthma prevalence is higher in areas of higher Westernization. Regardless of country, the prevalence of wheeze is high. Breathing medication use is high and similar reports from all countries. Children in areas of less Westernization may be at risk of asthma under-diagnosis.